2023
DOI: 10.1371/journal.pone.0281404
|View full text |Cite
|
Sign up to set email alerts
|

Denuded Descemet’s membrane supports human embryonic stem cell-derived retinal pigment epithelial cell culture

Abstract: Recent clinical studies suggest that retinal pigment epithelial (RPE) cell replacement therapy may preserve vision in retinal degenerative diseases. Scaffold-based methods are being tested in ongoing clinical trials for delivering pluripotent-derived RPE cells to the back of the eye. The aim of this study was to investigate human embryonic stem cell-derived retinal pigment epithelial (hESC-RPE) cells survival and behaviour on a decellularized Descemet’s Membrane (DM), which may be of clinical relevance in reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“… [ 37 ] Corneal Membrane Obtained by dissecting corneas of cattle/pigs Autologous RPE and IPE Monolayer cell patch was formed on Descement membrane Both cell types form a complete monolayer and microvilli structure on the membrane [ 38 ] Isolated from the donor human cornea and treated with thermolysin to remove the cells hESC-RPE hESC-RPE forms an intact monolayer on decellularized Descemet's membrane hESC-RPE cells successfully formed intact monolayers with mature tight junctions on decellularized Descemet membranes, displaying characteristic RPE cell morphology and protein localization, and gene expression analyses and VEGF secretion indicated that DM provided supportive scaffolding and inducible properties. [ 39 ] Lens Capsule The lens capsule was obtained by removal during cataract surgery, immersed in PBS at 37 ℃, UV-sterilized for 3 h, and subsequently digested with trypsin to remove cells. ARPE19 The cells are inoculated onto the capsular membrane of the lens to form a monolayer ARPE19 cells cultured on the lens capsule exhibited a monolayer with the presence of actin bands and tight junctions.…”
Section: Tissue Engineering Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“… [ 37 ] Corneal Membrane Obtained by dissecting corneas of cattle/pigs Autologous RPE and IPE Monolayer cell patch was formed on Descement membrane Both cell types form a complete monolayer and microvilli structure on the membrane [ 38 ] Isolated from the donor human cornea and treated with thermolysin to remove the cells hESC-RPE hESC-RPE forms an intact monolayer on decellularized Descemet's membrane hESC-RPE cells successfully formed intact monolayers with mature tight junctions on decellularized Descemet membranes, displaying characteristic RPE cell morphology and protein localization, and gene expression analyses and VEGF secretion indicated that DM provided supportive scaffolding and inducible properties. [ 39 ] Lens Capsule The lens capsule was obtained by removal during cataract surgery, immersed in PBS at 37 ℃, UV-sterilized for 3 h, and subsequently digested with trypsin to remove cells. ARPE19 The cells are inoculated onto the capsular membrane of the lens to form a monolayer ARPE19 cells cultured on the lens capsule exhibited a monolayer with the presence of actin bands and tight junctions.…”
Section: Tissue Engineering Materialsmentioning
confidence: 99%
“…Elena Daniele et al. [ 39 ] demonstrated that hESC-RPE could also attach and form a complete monolayer structure on Descemet's membrane isolated from human donor corneas and decellularized. The cell morphology, protein localization, VEGF secretion, and gene expression patterns were comparable to those of mature RPE.…”
Section: Tissue Engineering Materialsmentioning
confidence: 99%
“…Descemet’s membrane is another natural substrate with features resembling Bruch’s membrane characteristics concerning the abundant presence of type IV collagen, laminin and fibronectin. Daniele et al (2023) used this membrane to produce a polarized monolayer of human embryonic stem cell-derived retinal pigment epithelial (hESC-RPE) cells in vitro .…”
Section: Tissue Engineering Of the Retinal Pigment Epitheliummentioning
confidence: 99%